2009
DOI: 10.1111/j.1540-4560.2009.01607.x
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation and Conflict within Groups: Bridging Intragroup and Intergroup Processes

Abstract: Whereas intragroup processes and intergroup relations are often assumed to reflect discrete processes and cooperation and conflict to represent alternative outcomes, the present article focuses on intergroup dynamics within a shared group identity and challenges traditional views of cooperation and conflict primarily as the respective positive and negative outcomes of these dynamics. Drawing on the ideas, theories, and evidence presented in other articles in this volume, we (1) consider the dynamic tension bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 57 publications
2
48
0
1
Order By: Relevance
“…It is almost axiomatic, or at least apparently intuitive, that conflict within sides is often a significant cause of failed negotiations between them. And yet, outside of organizational studies (Dovidio, Saguy, & Shnabel, 2009), little empirical or applied work is done in this area when it comes to ethnic conflict and relations.…”
Section: Illustration: Policeàafrican American Relationsmentioning
confidence: 99%
“…It is almost axiomatic, or at least apparently intuitive, that conflict within sides is often a significant cause of failed negotiations between them. And yet, outside of organizational studies (Dovidio, Saguy, & Shnabel, 2009), little empirical or applied work is done in this area when it comes to ethnic conflict and relations.…”
Section: Illustration: Policeàafrican American Relationsmentioning
confidence: 99%
“…The issue closes with Dovidio, Saguy, and Shnabel (2009) examining the articles in this issue as a whole. They have eloquently concluded that when examining the relations between two subgroups that belong to and interact within the same group (i.e., society or organization) the traditional distinction between “intergroup” and “intragroup” processes is blurred, as both processes are highly interwoven.…”
Section: Organization Of the Issuementioning
confidence: 94%
“…In other words, participant interactions within intergroup settings are often a refl ection of interpersonal dynamics or social group interactions or a combination of the two. Th ose who are facilitating intergroup encounters, both intergroup and intragroup (Dovidio, Saguy, and Shnabel 2009), need to take these dynamics into account. …”
Section: Social Identity Theory and Intergroup Encountersmentioning
confidence: 99%